A geometria dos sólitons de Ricci compactos - Carlos, Elaine Sampaio de Sousa (2013)
The aim of this work is to study the geometry of the compact Ricci soliton, which correspond to self-similar solution of the Ricci flow. These manifolds are natural generalization to Einstein metrics. Here we shall prove that every compact Ricci soliton has positive scalar curvature. Moreover, we show that its fundamental group is finite. Finally, we prove that every compact Ricci soliton must be gradient.